2020
DOI: 10.1111/eci.13349
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and subclinical hypothyroidism on heart rate variability

Abstract: Background: We aimed to analyse if the effects of coexistent diabetes and subclinical hypothyroidism extend to the cardio autonomic nervous system, using heart rate variability baseline data from the Brazilian Longitudinal Study of Adult Health. Materials and Methods: Heart rate variability analyses were performed by linear time and frequency domains in 5-minute time series collected in the supine position. The associations of diabetes and subclinical hypothyroidism with the lowest quartile group for heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The LH-HF ratio is a sensitive marker of SVI [8]; hence, the increase in the LF-HF ratio represents considerable SVI in anti-TPOAb positive SCHypo. In the Poincaré indices (SD1 and SD2) of HRV, the width of SD1 reflects the parasympathetic modulation and the SD2 length reflects the sympathetic activity [14]. In our study, the SD1 value was profoundly decreased, and SD2 was increased in the antibody-positive SCHypo group than in controls, which can be used as a sensitive indicator of sympathovagal changes.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The LH-HF ratio is a sensitive marker of SVI [8]; hence, the increase in the LF-HF ratio represents considerable SVI in anti-TPOAb positive SCHypo. In the Poincaré indices (SD1 and SD2) of HRV, the width of SD1 reflects the parasympathetic modulation and the SD2 length reflects the sympathetic activity [14]. In our study, the SD1 value was profoundly decreased, and SD2 was increased in the antibody-positive SCHypo group than in controls, which can be used as a sensitive indicator of sympathovagal changes.…”
Section: Discussionmentioning
confidence: 46%
“…In anti-TPOAb positive SCHypo patients, a significant decrease in HFnu indicates decreased parasympathetic activity in these patients, as HFnu is an index of cardiac vagal drive [8,14]. This was supported by a significant reduction in TP of HRV in antibody-positive SCHypo patients compared with controls, like TP, in general, indicates the magnitude of vagal modulation of cardiac function [8,15].…”
Section: Discussionmentioning
confidence: 88%
“…The hypothalamus is involved in cardiac autonomic control and TSH release [ 60 , 61 ], linking the thyroid to the autonomic nervous system [ 62 , 63 ]. In hypothyroidism, the cardiac autonomic alteration may take place at an hypothalamic level [ 64 ]. Indeed, some studies suggested that TSH stimulates sympathetic output from the central nervous system and acts as a neurotransmitter, playing a critical role in determining sympathovagal imbalance [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes: Both diabetes and subclinical hypothyroidism exerted a combined impact on cardiac autonomic control and heart rate 31 . Postmenopausal women have been associated with a higher occurrence of subclinical hypothyroidism (SH) and the insulin resistance (IR) syndrome, which is related to type 2 diabetes mellitus, dyslipidaemia, and non-alcoholic fatty liver disease (NAFLD), hypertension in postmenopausal women, and obesity.…”
Section: Cognitive Damagementioning
confidence: 99%